Characteristic Differences of Thermal Runaway Triggered by Overheating and Overcharging in Lithium-Ion Batteries and Multi-Dimensional Safety Protection Strategies - Yao Yao; Lu Liu; Juan Gu; Haozhe Xing; Huachao Liu; Yihao Cheng; Youning Wang; Songlin Yue; Yanyu Qiu; Zhi Zhang (Batteries)
Overheating and overcharging are the core triggering conditions for the thermal runaway of lithium-ion batteries. Studying the behavioral differences of thermal runaway of lithium-ion batteries under these two conditions is crucial for the safety design and protection of lithium-ion batteries. In this study, we investigated the temperature, pressure, gas generation, and heat generation characteristics of lithium batteries under these two conditions. Under overheating conditions, the release of lattice oxygen in the cathode and the decomposition of the electrolyte trigger a self-catalytic reaction, generating CO2 (54.7%) and H2 (29.7%), with a total heat release of 17.6 kJ and a heat accumulation rate of 24.3 W, forming a local high-temperature core area. Under overcharging conditions, the voltage drop, capacity attenuation of 21.1% (2230→1762 mAh), and internal resistance surge (6→21 mΩ) reflect severe damage to the electrode. Accompanied by the oxygenation of the EC electrolyte (CO32− + C2H4↑), the gas production rate is faster. The middle pressure was 0.601 MPa, and the proportion of CO2 was 67.4%. However, the triggering of thermal runaway relies on the synergistic effect of internal electrochemical reactions and ohmic heat accumulation, resulting in a relatively low rate of energy accumulation.